Pengaruh Current Ratio, Debt to Equity Ratio, dan Debt to Asset Ratio Terhadap Net Profit Margin - Diah Ayu Puspita; Fazhar Sumantri; Theysa Sahlani Pratiwi (CV. ITTC INDONESIA, 2026)
Business competition is becoming increasingly intense, requiring companies to maintain financial performance to ensure business sustainability and improve profitability. One of the profitability indicators commonly used is Net Profit Margin (NPM), which may be influenced by a company’s liquidity and solvency conditions. However, previous studies examining the effects of Current Ratio (CR), Debt to Equity Ratio (DER), and Debt to Asset Ratio (DAR) on NPM have produced inconsistent findings.This study aims to analyze the effects of Current Ratio (CR), Debt to Equity Ratio (DER), and Debt to Asset Ratio (DAR) on Net Profit Margin (NPM) at PT Hexindo Adiperkasa Tbk during the 2000–2024 period. This research employed a quantitative approach with an associative research design. The data used were secondary data obtained from the annual financial statements of PT Hexindo Adiperkasa Tbk for the period 2000–2024. The population consisted of all published financial statements of the company, and a saturated sampling technique was applied, resulting in 25 observations. Data were collected through documentation methods and analyzed using multiple linear regression with IBM SPSS Statistics 26. The results indicate that, partially, Current Ratio, Debt to Equity Ratio, and Debt to Asset Ratio have no significant effect on Net Profit Margin, with significance values of 0.247, 0.863, and 0.634, respectively. Simultaneously, the three variables also have no significant effect on Net Profit Margin, with a significance value of 0.622. The coefficient of determination (R²) of 0.079 indicates that the model explains only 7.9% of the variation in Net Profit Margin. Therefore, the profitability of PT Hexindo Adiperkasa Tbk is influenced not only by liquidity and solvency ratios but also by other factors outside the research model.